Perceived Stress and Coping Strategies among Adolescent Girls on Pubertal Changes in a Selected Schools, Mangaluru - Fernandes, Sumitha; Zacharias, Roselin; Noronha, Wilma Shalini; Dsouza, Deepthi Gladsy (Journal of Health and Allied Sciences NU, 2024)
Background Adolescence represents a pivotal stage marked by various physical, psychological-emotional, and social transformations. Among these changes, puberty stands out as a significant characterized by hormonal shifts, physical alterations, and emotional fluctuations.Objectives The present study was aimed to assess perceived stress and coping strategies and find the relationship among adolescent girls on pubertal changes in a selected school in Mangaluru.Materials and Methods The study adopted the descriptive survey design among 205 adolescent girls recruited by using convenient sampling technique. Data were collected using self-developed stress rating scale and standardized brief-COPE.Results The study findings showed that the majority of the adolescent girls attained menarche at the age of 12 to 13 years and 72.7% of the adolescent girls perceived less level of stress, while 98% of the adolescent girls employed ineffective coping strategies on pubertal changes. The study findings also found that there was a moderate positive correlation between perceived stress and coping strategies (r = 0.480) among adolescent girls on pubertal changes.Conclusion The study concluded that adolescent girls have less stress on pubertal changes and employ ineffective coping strategies during pubertal changes.
Keywords: adolescent; coping; perceived; pubertal changes; strategies; stress